Asma Onset Dewasa Pada Wanita Berusia 41 Tahun : Laporan Kasus - Maulana Idham Lutfi (CV. Jasa Sukses Abadi, 2026)
Asthma is a chronic inflammatory disease of the airways that may first present in adulthood and often exhibits clinical characteristics that differ from those of childhood-onset asthma. Adult-onset asthma tends to be persistent, less responsive to standard therapy, and influenced by environmental and psychosocial factors. This case report aims to describe the management of adult-onset asthma using a holistic family medicine approach in a primary health care setting. The case involves a 41-year-old woman who experienced recurrent episodes of shortness of breath over the past approximately ten years, with no history of asthma or allergic disease during childhood. Her symptoms were triggered by dust, smoke, cold air, fatigue, and stress, and worsened after moving to a home environment with limited ventilation. The diagnosis of asthma was established clinically based on characteristic respiratory symptoms and a favorable response to bronchodilator therapy. Interventions were implemented using patient-centered, family-focused, and community-oriented approaches, including pharmacological therapy, health education, home environmental modification, and promotion of clean and healthy lifestyle behaviors. Evaluation was conducted through monitoring of clinical symptoms, behavioral changes, and pre- and post-intervention knowledge assessments. After three visits, the patient demonstrated a reduced frequency of exacerbations, improved understanding of the disease and adherence to treatment, increased ability to avoid triggering factors, and improved home environmental conditions. A holistic family medicine approach plays an important role in improving symptom control and quality of life in patients with adult-onset asthma.